The Lichen Genus Usnea On Quercus Suber In Iberian Cork-Oak Forests (The Lichenologist, 2000)
Fifteen species of Usnea are recorded from Iberian cork-oak forests: U. ceratina, U. cornuta, U. dasaea, U. esperantiana, U. ﬂammea, U. fulvoreagens, U. glabrata, U. hirta, U. mutabilis, U. rubicunda, U. subcornuta, U. subﬂoridana, U. subscabrosa, U. substerilis and U. wasmuthii. A key for these species is provided. Details of morphology, chemistry, distribution, ecology and taxonomy are discussed. Usnea dasaea is reported as new to the Iberian Peninsula. New chemotypes of U. fulvoreagens (with squamatic acid) and U. wasmuthii (with psoromic acid) have been identiﬁed. Distribution maps of U. dasaea and U. subcornuta in Europe are presented. A new combination, Usnea subﬂoridana subsp. praetervisa (Asahina) P. Clerc, is proposed